Perbandingan Hasil Pemeriksaan Urinalisis Menggunakan Metode Dipstick Dan Mikroskopik Di Klinik Bintang Timur Kota Sorong - Junaiddin, Junaiddin; Etnis, Baktianita Ratna; Letsoin, Paulina (Health Information : Jurnal Penelitian, 2023)
Urinalysis is an important clinical tool used for screening, diagnosis, and monitoring of diseases of the urinary system, and diseases can be detected through the system. analytic with a cross sectional approach to see the similarities or differences in the results of urinalysis examination using dipstick and microscopic methods. The sampling technique used is total sampling, namely the number of samples is the same as the population. The study was conducted from March to April 2020. The number of samples was 30 samples. The results showed that there were differences in the results of urinalysis examinations between the dipstick and microscopic methods where the results of the same leukocyte examination contained 13 samples with a presentation of 43% and the results were not the same there were 17 samples with the presentation of 57% while the results of the erythrocyte examination showed the same results there were 22 samples with a presentation of 73% and the results were not the same there were 8 samples with a presentation of 27%. The conclusion from the results of urinalysis using the dipstick and microscopic methods, there are differences in the number of leukocytes and erythrocytes. Suggestions from researchers for health workers who will carry out urinalysis examinations are that they should carry out dipstick and microscopic examinations carried out simultaneously and always be guided by standard operating procedures so that more accurate results can be obtained.